Trace Level Determination of Polyether Ionophores in Feed - Rokka, Mervi (Hindawi Publishing Corporation, 2013)
A liquid chromatography-mass spectrometric method was developed and validated to determine six polyether ionophores (lasalocid sodium, monensin sodium, salinomycin sodium, narasin, maduramicin ammonium alpha, and semduramicin sodium) in feed samples. The method developed was very straightforward, involving extraction with 84% acetonitrile of the coccidiostats from the feed samples and filtration of the raw extract prior to chromatographic analysis. Method validation included the determination of selectivity, linearity, specificity, repeatability, the limit of detection, limit of quantification, decision limit (CCα), detection capability (CCβ), and recovery. Feed samples from the Finnish national feed control programme and suspected carry-over samples from a feed manufacturer were analysed in parallel with an existing liquid chromatography method coupled with ultraviolet detection. All feed control samples were negative in LC-UV, but with the developed MS method, monensin, salinomycin, and narasin were detected at concentrations of <0.025–0.73 mg/kg, <0.025–0.027 mg/kg, and <0.025–1.6 mg/kg, respectively. In suspected carry-over samples after an output of 2.0 tonnes of unmedicated feed in the pelletizer line, the concentrations of monensin, salinomycin, and narasin varied from undetected to 16 mg/kg. In the mixer line, after 3.2 tonnes of unmedicated feed output, the concentrations of monensin, salinomycin, and narasin varied from undetected to 2.4 mg/kg.